Effect of 2-chloro-substitution of adenine moiety in mixed-ligand gold(I) triphenylphosphine complexes on anti-inflammatory activity: the discrepancy between the in vivo and in vitro models - Hošek, Jan; Vančo, Ján; Štarha, Pavel; Paráková, Lenka; Trávníček, Zdeněk (PloS one, 2013)
A series of gold(I) triphenylphosphine (PPh3) complexes (1-9) involving 2-chloro-N6-(substituted-benzyl)adenine derivatives as N-donor ligands was synthesized and thoroughly characterized by relevant methods, including electrospray-ionization (ESI) mass spectrometry and multinuclear NMR spectroscopy. The anti-inflammatory and antiedematous effects of three representatives 1, 5 and 9 were evaluated by means of in vitro model based on the expression of pro- and anti-inflammatory cytokines and influence of the complexes on selected forms of matrix metalloproteinases secreted by LPS-activated THP-1 monocytes and in vivo model evaluating the antiedematous effect of the complexes in the carrageenan-induced rat hind-paw edema model. In addition to the pharmacological observations, the affected hind paws were post mortem subjected to histological and immunohistochemical evaluations. The results of both in vivo and ex vivo methods revealed low antiedematous and anti-inflammatory effects of the complexes, even though the in vitro model identified them as promising anti-inflammatory acting compounds. The reason for this discrepancy lies probably in low stability of the studied complexes in biological environment, as demonstrated by the solution interaction studies with sulfur-containing biomolecules (cysteine and reduced glutathione) using the ESI mass spectrometry.
Keywords: Adenine; Ligands; techniky in vitro; ligandy; zlato; antiflogistika; cytokiny; organofosforové sloučeniny; Edema; ELISA; krysa rodu Rattus; zvířata; Enzyme-Linked Immunosorbent Assay; potkani Wistar; buněčné linie; hmotnostní spektrometrie s elektrosprejovou ionizací; adenin; Cell Line; Rats, Wistar; edém; Cytokines; Organophosphorus Compounds; In Vitro Techniques; Rats; Anti-Inflammatory Agents; Spectrometry, Mass, Electrospray Ionization; Animals; Gold